ChemInform Abstract: Stereoselective Total Synthesis of Cochliomycin A. Issue 35 (2nd September 2014) - Wang, Linlin; Gao, Yangguang; Liu, Jun; Cai, Chao; Du, Yuguo
Abstract The stereoselective synthesis of the title compound (I) from L‐arabinose is reported.